Game Development is Developmentally Appropriate Practice (Developmentally Appropriate) Practice Based Education for Elementary School Children - Ruben Pardamean Hutapea; Nurhayati Simatupang; Indra Kasih (Universitas Negeri Medan, 2021)
This study aims to: The purpose of this study is to develop games in physical education subjects in schools based on DAP (Developmentally Appropriate Practice). Then in this study will produce a product in the form of a game module with the concept of DAP (Developmentally Appropriate Practice) for basic locomotor movements. This type of research is development research based on the Borg and Gall model. The trial subjects consisted of material experts, game experts, and physical education teachers at the Imanuel Medan Elementary School and Methodist 1 Medan. The first stage of this model is the needs research stage, followed by the design stage, and the third stage is development and implementation. In this stage, all stages involve an evaluation and revision process. The assessment of the material expert is 89%, the game expert is 90.8%, and the results of the evaluation of the sports teacher in the first stage is 73.8%, and the second stage is 86%. Results The results of the product assessment have increased with a significant difference of 12.2%. This shows that the product developed on locomotor motion material through game development based on DAP (Developmentally Appropriate Practice) is feasible to be used in the implementation of learning.